A responsibility to protect : obligations of states and the international community to prevent genocide under existing and developing norms of public international law with an emphasis on the obligations of ‘fragile states’. - Bradley, Martha (University of Pretoria, 2024)
Dissertation (LLM (Public International Law))--University of Pretoria, 2023.